Artificial intelligence as a design tool for a printing shop - Meshcheriakova, A.; Kulishova, N. (Universidad de Guanajuato Primera Edición, 2025)
With the development of artificial intelligence (AI), it has also affected the publishing and printing business, as AI can simplify and speed up work at the stage of design, printing, checking for defects, etc. [1]. However, the use of AI is not always appropriate, as it has its specifics according to the work of each printing business and must be investigated separately.
Keywords: Artificial intelligence; printing shop